First characterization of methanogens in oral cavity in Malian patients with oral cavity pathologies - Elisabeth Sogodogo; Ogobara Doumbo; Gérard Aboudharam; Bourema Kouriba; Ousseynou Diawara; Hapssa Koita; Souleymane Togora; Michel Drancourt (BMC, 2019)
Abstract Background The oral cavity of humans is inhabited by several hundreds of bacterial species and other microorganisms such as fungi and archaeal methanogens. Regarding methanogens, data have been obtained from oral cavity samples collected in Europe, America and Asia. There is no study published on the presence of methanogens in the oral cavity in persons living in Africa. The objective of our study was to bring new knowledge on the distribution of oral methanogens in persons living in Mali, Africa. Methods A total of 31 patients were included in the study during a 15-day collection period in September. Bacterial investigations consisted in culturing the bacteria in 5% sheep blood-enriched Columbia agar and PolyViteX agar plates. For archaeal research, we used various methods including culture, molecular biology and fluorescent in situ hybridization (FISH). Results Eight of 31 (26%) oral samples collected in eight patients consulting for stomatology diseases tested positive in polymerase chain-reaction (PCR)-based assays for methanogens including five cases of Methanobrevibacter oralis and one case each of Methanobrevibacter smithii, Methanobrevibacter massiliense and co-infection Methanobrevibacter oralis and Methanobrevibacter massiliense. Conclusions In this pilot study, we are reporting here the first characterization of methanogens in the oral cavity in eight patients in Mali. These methanogen species have already been documented in oral specimens collected from individuals in Europe, Asia, North America and Brazil.